2013
DOI: 10.1128/jcm.01244-13
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak Caused by an Ertapenem-Resistant, CTX-M-15-Producing Klebsiella pneumoniae Sequence Type 101 Clone Carrying an OmpK36 Porin Variant

Abstract: Although numerous studies have documented outbreaks of carbapenem-resistant Klebsiella pneumoniae (CRKP) possessing various carbapenemases, reports on outbreaks due to CRKP possessing extended-spectrum ␤-lactamases (ESBLs) and/or AmpCs with porin lesions have been limited. Here, we describe an outbreak caused by an ertapenem-resistant, CTX-M-15-producing clonal K. pneumoniae strain expressing an OmpK36 porin variant. From May 2012 to November 2012, 37 ertapenem-resistant K. pneumoniae isolates phenotypically n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
43
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 40 publications
4
43
0
1
Order By: Relevance
“…These strains were highly resistant to carbapenems, but only susceptible to polymyxin and tigecycline, which have been ultimately considered as the last-resort treatment for such infections. Previous research demonstrated that antimicrobial-resistant K. pneumoniae isolates could carry multiple resistance genes simultaneously [13,14]. In our study, a high prevalence of β-lactamase genes was observed.…”
Section: Discussionsupporting
confidence: 49%
“…These strains were highly resistant to carbapenems, but only susceptible to polymyxin and tigecycline, which have been ultimately considered as the last-resort treatment for such infections. Previous research demonstrated that antimicrobial-resistant K. pneumoniae isolates could carry multiple resistance genes simultaneously [13,14]. In our study, a high prevalence of β-lactamase genes was observed.…”
Section: Discussionsupporting
confidence: 49%
“…This sequence type was associated with various β-lactam resistance mechanisms in different parts of the world: CTX-M-15 production in France, Greece and Italy; SHV-12 production in the Czech Republic; OXA-48 production in Spain, Libya, France, Tunisia, Morocco, Switzerland and South Africa; KPC-2 production in Italy and Spain [32,[35][36][37][38][39][40][41][42]. In our institution the presence of CTX-M-15 producing ST101 seemed to be restricted both timely and spatially, as the majority of the isolates originated from a single department with a decreasing incidence ( Tables II and III).…”
Section: Discussionmentioning
confidence: 99%
“…Beside several minor clones, three internationally disseminated CTX-M-15 producing K. pneumoniae clones, namely ST15, ST101 and ST147 were present in the Clinical Centre University of Pécs, of which ST15 and ST147 are considered to be epidemic clones in Hungary [6,[32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, nosocomial outbreaks by carbapenem-resistant strains were recently documented in which resistance was not mediated by carbapenemases [13][14]. In conclusion, this study demonstrates the rapid acquisition of decreased carbapenem susceptibility in ESBL-producing K. pneumoniae clinical isolates.…”
mentioning
confidence: 69%
“…Previous research indicates that ESBL expression in combination with the loss of porin expression can reduce susceptibility to carbapenems in clinical K. pneumoniae and E. coli isolates [10][11][12]. Whilst numerous outbreaks of carbapenem-resistant K. pneumoniae possessing various carbapenemases have been documented; an outbreak caused by an ertapenem-resistant, CTX-M-15-producing clonal K. pneumoniae strain expressing an OmpK36 porin variant was only recently described [13][14].…”
mentioning
confidence: 99%